Optimal control for quadruple inverted pendulum - Nguyen , Văn Đông Hải; Nguyen , Phong Lưu; Nguyen, Minh Tâm; Hoang, Ngọc Văn (Journal of Technical Education Science, 2015)
Inverted pendulum is a SIMO model (single-input and multi-output) which is popular in testing automatic control algorithm. The more degrees of freedom that an inverted pendulum system has, the more outputs that an input of the system has to control. This makes difficulties in controlling multilink inverted pendulum. This paper presents optimal control algorithms (LQR) in balancing the system in vertical upward-position. Matlab/Simulink simulation results show that the system is stabilized well around the absolute upward-position and also around other working points.